The Evaluation of the Employment of Migrants by Employees - Dajnoki, Krisztina; Kőmíves, Péter Miklós (International Journal of Engineering and Management Sciences, 2017)
The exploration of specifications of the employee groups endangered in the labour market, and their socialand labour market integration have always been a challenging task for the professionals. As a result of thedomestically also appeared migrant wave, the actuality of the topic has even more increased. In this study -prepared in the framework of the research program „Human resource management challenges of the reception and labour market integration of the migrants” - we aimed to reveal the attitudes of employees about the labour market integration of the migrants. We have defined an objective to explore whether they are afraid of losing their current jobs, what factors influence the employment of the migrants and what kind of positive and negative effects they take on the society and economy. Based on the results of the survey we have found that employees are not afraid of migrants taking their jobs, still they are quite uncertain whether they would employ or work with a migrant person. Regarding the effect on the society and economy an unambiguous negative attitude was experienced.